(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the pattern of various dermatological diseases and demographic characteristics of admitted patients. Study Design: Retrospective study Place and Duration of Study: This study was Department of Dermatology MTI HMC Peshawar of 1st January 2022 to 31st December 2022. Methods: Diagnosis, demographic features and duration of stay for different skin diseases was recorded on prescribed Performa. A total of 323 patients were admitted for various dermatological diseases. Results: Out of 323 patients 182 (56%) were male and 141 (44%) were female. Among 323 patients, 48 (15%) were in age range of 0 day to 14 years, 149 (46%) in age group of 15 years to 45 years and 125 (39%) were > 45 years of age.88 (27.2%) patients with various types of eczemas presented for hospitalization, followed by Psoriasis with 40 (12.3%) patients, immunobullous diseases in 40 (12.3%), and 36 (11%) having different skin infections. The high number of patients i.e. 167 (52%) belonged to Peshawar while the lowest patients 3 (0.9%) were admitted from Hazara Division. Majority of patients were farmers followed by labourers, government servants, shopkeepers, teachers, drivers and tailors. Mean duration of hospital stay was 7.42 days. Hospitalization is necessary for patients with multiple dermatological diseases and comorbidities. Numerous skin diseases are chronic in nature and requires prolonged hospital stay. Therefore, expanding specialized dermatological inpatient facilities is necessary. Conclusion: Hospitalization is necessary for patients with multiple dermatological diseases and comorbidities. Numerous skin diseases are chronic in nature and requires prolonged hospital stay. Also as many dermatological emergencies are admitted in skin wards so there is need for high dependency suit with specialized monitoring facilities and nursing care in every skin unit.